2012
DOI: 10.4194/1303-2712-v12_2_15
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Growth and histology of intestine and liver of carp fed diets with or devoid of fish meal (FM) was studied. Carp were fed four experimental diets formulated to contain 38% protein for 90 days. FM was incorporated at 30% in feed A, 15% in feed B and C, and was completely replaced with a mixture of plant proteins in feed D. Feed C and D were supplemented with methionine and lysine. The results showed that carp fed feed D had the lowest weight gain, length and height compared to the other three diets, whereas no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Tilapia are omnivorous fi sh, so they do not require high inclusion rate of FM, and do need greater amounts of Σ n-6 PUFA than Σ n-3 PUFA in their diets (Takeuchi et al 2002, Gümüş andErdogan 2010). Evaluation of histological structure of fi sh liver is important to assessing the effects of various nutrient feedstuffs that use raw materials in diet (Caballero et al 2004, Rašković et al 2011, Marković et al 2012, Hu et al 2013. In the presently reported study, the liver of fi sh fed the experimental diets demonstrated normal-shaped hepatocytes but, lower lipid ac- Glencross et al (2004) reported that small lipid droplet formation in the liver of rainbow trout was observed, which may in part be related to the poorer energy retention of a diet that included high levels of yellow lupin kernel meal.…”
Section: Discussionmentioning
confidence: 99%
“…Tilapia are omnivorous fi sh, so they do not require high inclusion rate of FM, and do need greater amounts of Σ n-6 PUFA than Σ n-3 PUFA in their diets (Takeuchi et al 2002, Gümüş andErdogan 2010). Evaluation of histological structure of fi sh liver is important to assessing the effects of various nutrient feedstuffs that use raw materials in diet (Caballero et al 2004, Rašković et al 2011, Marković et al 2012, Hu et al 2013. In the presently reported study, the liver of fi sh fed the experimental diets demonstrated normal-shaped hepatocytes but, lower lipid ac- Glencross et al (2004) reported that small lipid droplet formation in the liver of rainbow trout was observed, which may in part be related to the poorer energy retention of a diet that included high levels of yellow lupin kernel meal.…”
Section: Discussionmentioning
confidence: 99%
“…10). Markovic et al (2012) observed increased leucocytes infiltration in the epithelium often accompanied by increased mucous production when carp was fed with plant origin feed. Baeverfjord and Krogdahl (1996) and Uran et al (2008) reported enteritis which involved inflammatory infiltrate in fish intestine fed with soybean meal.…”
Section: Resultsmentioning
confidence: 88%
“…These samples were immediately fixed in 10% neutral buffered formalin and processed following standard histological procedures i.e., dehydrated in ascending series of ethanol concentrations, and embedded in paraffin. Tissue sections were cut at 4-5 μm, stained with hematoxylin and eosin (Humason, 1979;Markovic et al, 2012).…”
Section: Histologymentioning
confidence: 99%
“…ini dapat disebabkan oleh racun, infeksi, ataupun trauma sel (Raskovic, 2010). Kematian sel seperti ini akan menyebabkan fungsi hati menjadi menurun, proses detoksifikasi racun yang ada dalam tubuh akan semakin terhambat yang kemudian dapat menyebabkan ikan menjadi keracunan (Ayotunde, 2011 (Lewis, 1986).…”
Section: Hepatocyte F O C a L Necrosis Focal Necrosis Focal Necrosisunclassified